2022
DOI: 10.1002/chem.202104182
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Conformational Space of SARS‐CoV‐2 RNA Quadruplex RG‐1 by Cellular Components and the Amyloidogenic Peptides α‐Synuclein and hIAPP

Abstract: Given the emergence of the severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2), which particularly threatens older people with comorbidities such as diabetes mellitus and dementia, understanding the relationship between Covid-19 and other diseases is an important factor for treatment. Possible targets for medical intervention include G-quadruplexes (G4Qs) and their protein interaction partners. We investigated the stability and conformational space of the RG-1 RNA-G-quadruplex of the SARS-CoV-2 N-gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 76 publications
1
16
0
Order By: Relevance
“…Although the CD spectra of RG-1 in Na + and K + containing buffer (black lines in Figure 6 , panels C and D) exhibit the same general features, the intensities of the bands are different. In particular in the presence of Na + , the positive band is less intense with respect to that in K + , indicating that the RG-1 is not fully folded or, most likely, a population of (partially) unfolded conformers coexist, as also previously observed in single-molecule FRET experiments [ 34 ]. Indeed, the spectrum of the fully unfolded RG-1 recorded at 75 °C shows a positive band around 270 nm, which is less intense with respect to the same band at 25 °C (see Supplementary Figure S4 ).…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Although the CD spectra of RG-1 in Na + and K + containing buffer (black lines in Figure 6 , panels C and D) exhibit the same general features, the intensities of the bands are different. In particular in the presence of Na + , the positive band is less intense with respect to that in K + , indicating that the RG-1 is not fully folded or, most likely, a population of (partially) unfolded conformers coexist, as also previously observed in single-molecule FRET experiments [ 34 ]. Indeed, the spectrum of the fully unfolded RG-1 recorded at 75 °C shows a positive band around 270 nm, which is less intense with respect to the same band at 25 °C (see Supplementary Figure S4 ).…”
Section: Resultssupporting
confidence: 62%
“…However, a more likely explanation may be found in the details of the conformational dynamics of RG-1. It was previously shown that not all RG-1 molecules in Na + solution are fully folded in a parallel conformation [ 34 ]. Single-molecule FRET data are rather consistent with a significant fraction of (partially) unfolded (~50%) states also being present.…”
Section: Discussionmentioning
confidence: 99%
“…N-protein of SARS-CoV-2 plays an important role in controlling the replication and assembling of viruses, which is also an important target to fight against the virus. Mukherjee et al ( 2022 ) found the amyloid proteins hIAPP and α-Synuclein can stabilize the partial folded conformation and completely folded conformation of RG-1 G4Q (RNA-G-quadruplex formed by putative G-quadruplex forming sequence RG-1 which locates in the coding sequence region of SARS-CoV-2 nucleocapsid phosphoprotein), respectively. RG1 G4Q can inhibit the translation of mRNA of the SARS-CoV-2 N-protein (Zhao et al 2021 ).…”
Section: Effects Of Amyloid Peptides Against Microbes and The Possibl...mentioning
confidence: 99%
“…Now, this is a rapidly developing research field. When we were almost finished with this review, Mukherjee et al reported modulation of the conformational space of RG-1 G4 in SARS-CoV-2 by cellular components and two amyloidogenic peptides, α-Syn and hIAPP, which are involved in Parkinson's disease and type-II diabetes [148] . These peptides stabilized RG-1 folding in a sequence-specific way, which was different from their interaction with human telomeric G4.…”
Section: Regulation Of Sars-cov-2 G4s By Proteinsmentioning
confidence: 99%